Politik Urban Kebijakan Pemerintah Kota Palembang dalam Penataan Kabel Listrik - Risma Dewi Hartanti; Ainur Ropik; Reni Apriani (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study examines the dynamics of urban politics in the policy of the Palembang City Government regarding the management of disorganized electrical cables. The problem of irregularly hanging cables, mixed with telecommunication lines, and often dangling too low poses safety risks, reduces the city’s aesthetics, and reflects weak governance of urban infrastructure. This research employs a qualitative approach using a case study method. Data were collected through field observations, in-depth interviews with relevant stakeholders, and documentation. The research informants consisted of representatives from the Palembang City Government, PLN (the state electricity company), telecommunication providers, and affected communities. The findings indicate that cable management policy is a concrete effort by the government to create an orderly, safe, and modern urban spatial arrangement. The Palembang City Government seeks to reorganize the overhead cable networks while simultaneously planning the development of underground utility ducts as a long-term solution. However, the implementation of this policy faces several challenges, particularly conflicting interests among stakeholders: PLN emphasizes operational efficiency, telecommunication providers resist additional financial burdens, while the public demands quick action but shows limited participation. This study concludes that the issue of cable management is not merely technical but also represents an arena of urban political contestation among the state, the private sector, and society. Effective solutions require cross-sectoral coordination, strong regulatory frameworks, collaborative financing, and active community involvement. Through a comprehensive approach, cable management in Palembang City has the potential to enhance public safety, improve urban aesthetics, and strengthen government legitimacy in sustainable urban governance.